MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN VIDEO SCREENCAST POWER POINT UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS - Setiyanto, Agus; Tandililing, Edy; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research purposed to explain: The difference of mathematic communication ability between the students who get Problem Solving Learning Model with screencast powerpoint video and powerpoint; The relation between mathematic communication ability and student’s activity in Problem Solving Learning Model with screencast powerpoint; The learning achievement in Problem Solving Learning Model with screencast powerpoint. This research is equivalent material design and the population are all the ninth grade students of SMP N 1 Menyuke that consist of six classes. The sample are two classes taken randomly, one class is chosen as experiment class and the other classes are as control classes.The experiment classes are applied Problem Solving Learning Model with screencast powerpoint video and control class with Problem Solving Learning Model with powerpoint. The instrument of this research are student’s worksheet monitoring and mathematic communication ability test. The result of analysis data use independent sample t test, the correlation analysis and one sample t test show that: There is significant difference of the mathematic communication ability between experiment class and control classes; There is positive corelation (high category) between the mathematic communication ability and student’s activity in experiment classes; Students get good learning achievement and good mathematic communication ability. Keyword: Problem Solving Learning Model with screencast powerpoint video, mathematic communication ability, student’s activity